Uno Stacko Game Media Development About Understanding People's Conformity in Class VII Students at SMP Negeri 15 Yogyakarta - Farhah Prihasti Anggraeni; Ulfa Danni Rosada (Universitas Cokroaminoto Palopo, 2020)
Teenagers cannot be called children or adults, they have new tasks in the development of their lives. If adolescents fail to develop their own identity, they will lose direction and have an impact on their behavior, become deviant, the development of this identity is usually influenced by their friends in school. Schools are not only used as places for education, schools are also places for teenagers to socialize and equalize existing norms. The adjustment process carried out by adolescents is called peer conformity. The adjustment of these norms has an impact on the number of adolescents who mistake socializing only to be recognized by their peers. Peer conformity has two impacts on students, namely positive and negative. Group guidance is an activity carried by a group of people by taking advantage of group dynamics. Uno stacko in the form of colorful blocks, this media is an educational medium that can improve cognitive. The purpose of developing this research is to develop uno stacko game media about understanding peer conformity that can be used by guidance and counseling teachers as a service medium in schools. This study uses a Research and Development (R&D) type of research using the Brog and Gall model until the 5th stage. The data collection technique is in the form of an assessment sheet. Data analysis used qualitative and quantitative analysis. The results obtained test gets a score of 87.5 very good criteria, the media test gets a score of 87.5 very good criteria, and the service test gets a theory score of 88.46 very good criteria. Therefore, based on the assessment of the three experts above, the Uno Stacko game media on understanding peer conformity in class VII students at SMPN 15 Yogyakarta is declared feasible to use.